2020
DOI: 10.3390/cells9020270
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Export of Cyclin B Mediated by the Nup62 Complex Is Required for Meiotic Initiation in Drosophila Males

Abstract: Background: The central channel of the nuclear pore complex plays an important role in the selective transport of proteins between the nucleus and cytoplasm. Previous studies have demonstrated that the depletion of the Nup62 complex, constructing the nuclear pore channel in premeiotic Drosophila cells, resulted in the absence of meiotic cells. We attempted to understand the mechanism underlying the cell cycle arrest before meiosis. Methods: We induced dsRNAs against the nucleoporin mRNAs using the Gal4/UAS sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 71 publications
3
19
3
Order By: Relevance
“…Two cysts contained spermatids that each harbored a single Nebenkern and a larger single nucleus (Table 2). As mentioned above, these phenotypic characteristics were similar to those of meiotic mutants with failure of meiosis initiation (Inoue et al., 2012; Okazaki et al., 2020; White‐Cooper et al., 1993, 1998), suggesting that Hsc70‐4 is crucial for meiosis initiation. Our investigation revealed that in Drosophila testes, the silencing of either Hsc70‐3 or Hsc70‐4 led to cell growth arrest in the phases S3 and S4, respectively.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Two cysts contained spermatids that each harbored a single Nebenkern and a larger single nucleus (Table 2). As mentioned above, these phenotypic characteristics were similar to those of meiotic mutants with failure of meiosis initiation (Inoue et al., 2012; Okazaki et al., 2020; White‐Cooper et al., 1993, 1998), suggesting that Hsc70‐4 is crucial for meiosis initiation. Our investigation revealed that in Drosophila testes, the silencing of either Hsc70‐3 or Hsc70‐4 led to cell growth arrest in the phases S3 and S4, respectively.…”
Section: Resultssupporting
confidence: 71%
“…We used anti‐HA and anti‐Akt antibodies (C67E7, #4691, Cell Signaling, Danvers, MA, USA) to identify complexes containing Hsc70‐2‐HA and Akt. PLA in situ (Sigma‐Aldrich Co., MO, USA) was performed according to a method described previously (Okazaki et al., 2020). The specimens were stained with DAPI and then mounted using VECTASHIELD Mounting Medium (#H‐1200, Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proximity ligation assay (PLA), which enables detection of protein interactions within a cell, was performed according to the Duolink kit method (Nacalai Inc., Kyoto, Japan) as described previously ( Okazaki et al, 2020 ). We applied the PLA method to examine a close association between Cp110 and GFP–Orbit.…”
Section: Methodsmentioning
confidence: 99%